2021
DOI: 10.1186/s12872-021-01931-9
|View full text |Cite
|
Sign up to set email alerts
|

Is body mass index (BMI) or body adiposity index (BAI) a better indicator to estimate body fat and selected cardiometabolic risk factors in adults with intellectual disabilities?

Abstract: Background The BMI index cannot always be used in people with intellectual disabilities due to neuromuscular coordination disorders and psychological barriers that may hinder conventional body weight measurement. The study aimed to assess the usefulness of BMI and BAI in estimating obesity and body fat in people with intellectual disabilities. Methods The first stage of the research involved 161 people with profound intellectual disabilities. Soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…It is also important to recognize the importance of the BAI fatness index in terms of research protocols (the necessary measurements of somatic characteristics for calculating BAI are BH and HC) for older adults with co-morbidities of the musculoskeletal system who have difficulty adopting a habitual posture (thus making it difficult to measure body mass). Such a conclusion is consistent with findings reported by other authors [ 16 ] and those presented in our previous studies [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is also important to recognize the importance of the BAI fatness index in terms of research protocols (the necessary measurements of somatic characteristics for calculating BAI are BH and HC) for older adults with co-morbidities of the musculoskeletal system who have difficulty adopting a habitual posture (thus making it difficult to measure body mass). Such a conclusion is consistent with findings reported by other authors [ 16 ] and those presented in our previous studies [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…The body adiposity index (BAI) (BAI = hip circumference[cm]/(body height [m]) − 18) was also computed. BAI is believed to be an objective marker to evaluate body adiposity in both able-bodied and disabled populations [ 15 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However it has been shown that the body adiposity index (BAI) is a more reliable marker, especially for people with disabilities, e.g. amputees [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies by Zwierzchowska et al (2013Zwierzchowska et al ( , 2014Zwierzchowska et al ( , 2020bZwierzchowska et al ( , 2021 the BAI, in contrary to the BMI, seems to be a more reliable marker, especially for people with disabilities. Furthermore, Zwierzchowska et al (2020b) noticed that a higher BAI contributed to the deepening of the lumbar lordosis and LBP, what is consistent with the findings of Mirbagheri et al (2015).…”
Section: Tk -Thoracic Kyphosis; Pv -Physiological Values; Ll -Lumbar ...mentioning
confidence: 98%
“…As it was found, an inappropriate level of body fat mass (estimated by the body adiposity index (BAI)) has a negative influence on anteroposterior spinal curvatures, mainly by deepening the lumbar lordosis which contributes to low back pain (LBP) (Zwierzchowska and Tuz, 2018;Zwierzchowska et al, 2020b). To assess the level of fat mass, the body mass index (BMI) is usually used, however, it has been shown that the BAI is a more reliable marker, especially for people with disabilities (Zwierzchowska et al, 2013(Zwierzchowska et al, , 2020b(Zwierzchowska et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%